A Role for Insulin‐like Growth Factor 1 in the Generation of Epileptic Spasms in a murine model. Issue 1 (10th May 2022) - Ballester‐Rosado, Carlos J.; Le, John T.; Lam, Trang T.; Mohila, Carrie A.; Lam, Sandi; Anderson, Anne E.; Frost, James D.; Swann, John W.
Abstract : Objective: Infantile spasms are associated with a wide variety of clinical conditions, including perinatal brain injuries. We have created a model in which prolonged infusion of tetrodotoxin (TTX) into the neocortex, beginning in infancy, produces a localized lesion and reproduces the behavioral spasms, electroencephalogram (EEG) abnormalities, and drug responsiveness seen clinically. Here, we undertook experiments to explore the possibility that the growth factor IGF‐1 plays a role in generating epileptic spasms. Methods: We combined long‐term video EEG recordings with quantitative immunohistochemical and biochemical analyses to unravel IGF‐1's role in spasm generation. Immunohistochemistry was undertaken in surgically resected tissue from infantile spasms patients. We used viral injections in neonatal conditional IGF‐1R knock‐out mice to show that an IGF‐1‐derived tripeptide (1‐3)IGF‐1, acts through the IGF‐1 receptor to abolish spasms. Results: Immunohistochemical methods revealed widespread loss of IGF‐1 from cortical neurons, but an increase in IGF‐1 in the reactive astrocytes in the TTX‐induced lesion. Very similar changes were observed in the neocortex from patients with spasms. In animals, we observed reduced signaling through the IGF‐1 growth pathways in areas remote from the lesion. To show the reduction in IGF‐1 expression plays a role in spasm generation, epileptic rats were treated with (1‐3)IGF‐1. We provide 3 lines of evidence that (1‐3)IGF‐1 activates the IGF‐1 signaling pathway by acting through the receptor for IGF‐1. Treatment with (1‐3)IGF‐1 abolished spasms and hypsarrhythmia‐like activity in the majority of animals. Interpretation: Results implicate IGF‐1 in the pathogenesis of infantile spasms and IGF‐1 analogues as potential novel therapies for this neurodevelopmental disorder. ANN NEUROL 2022;92:45–60